Behavior of peripheral rods and their role in the life cycle of Myxococcus xanthus. - O'Connor, K A (1991)
Myxococcus xanthus is a gram-negative bacterium with a complex life cycle including a developmental phase in which cells aggregate and sporulate in response to starvation. In previous papers, we have described a heretofore unsuspected layer of complexity in the development of M. xanthus: vegetatively growing cells differentiate into two cell types during development. In addition to the differentiation of spores within fruiting bodies, a second cell type, peripheral rods, arises outside fruiting bodies. The pattern of expression of proteins in peripheral rods is different from that of either vegetatively growing cells or spores, and peripheral rods express a number of recognized developmental markers. In this report, we examine four aspects of the biology of peripheral rods: (i) the influence of nutrients on the proportion of peripheral rods in a population of developing cells, (ii) the capacity of peripheral rods to recapitulate development, (iii) the development of peripheral rods on conditioned medium, and (iv) the ability of peripheral rods to resume growth on low amounts of exogenously added nutrients. The results of these studies suggest that peripheral rods play a significant role in the life cycle of M. xanthus by allowing the exploitation of low amounts or transient influxes of nutrients without the investment of energy in spore germination. The differentiation of vegetatively growing cells into two cell types that differ significantly in biology, shape, and localization within the population has been incorporated into a model of the life cycle of M. xanthus.